Pterocladiella maribagoensis (Gelidiales, Rhodophyta), a new marine alga from Cebu, Philippines - Boo, Ga Hun; Geraldino, Paul John L. (Phytotaxa, 2016)
A new species of marine gelidioid red algae, Pterocladiella maribagoensis, is described and illustrated. Pterocladiella maribagoensis is distinguished by small, terete to compressed thalli with alternate or irregular branches, peg-like haptera, rhizines in medulla, and tetrasporangial sori without sterile margin at the terminal of branches. Analyses of both mitochondrial cox1 and plastid rbcL sequences revealed that P. maribagoensis was distinct from other species of Pterocladiella and clustered with P. australafricanensis, P. beachiae, P. caerulescens, P. phangiae, and P. psammophila. Morphological differences between P. maribagoensis and similar species are presented.